2021
DOI: 10.3389/fgwh.2021.705611
|View full text |Cite
|
Sign up to set email alerts
|

Easing of Regulatory Barriers to Telemedicine Abortion in Response to COVID-19

Abstract: For many people seeking abortion during the continuing COVID-19 pandemic, telemedicine abortion is the safest and most acceptable method, posing lower risk of exposure to the virus. In addition, by reducing in-person visits with health care providers, increased use of telemedicine for abortion can reduce pressure on overburdened health systems. Given the benefits of telemedicine during the pandemic, government agencies in several countries took measures to temporarily allow telemedicine abortion. We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Current guidelines recommend telehealth as an option for provision of abortion services (22), and it is accepted internationally as safe approach (23). In Australia prescribers are required to ensure that women have 24 h access to the provision of surgical uterine evacuation or other interventions required for the management of complications of medical abortion (24).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Current guidelines recommend telehealth as an option for provision of abortion services (22), and it is accepted internationally as safe approach (23). In Australia prescribers are required to ensure that women have 24 h access to the provision of surgical uterine evacuation or other interventions required for the management of complications of medical abortion (24).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…In United Sates, telemedicine for abortion care was considered safe, cost-effective, and the preferred method of abortion during acute periods of COVID-19 transmission ( 18 ). A study found examples of eight countries where governments removed regulatory barriers to the practice of telemedicine abortion in response to the pandemic ( 19 ). In the United Kingdom, on March 30, 2020, the Department of Health and Welfare liberalized the regulation of legal abortion for two years, or while the Coronavirus Law is in effect, allowing legal abortion service by telemedicine as a temporary measure broadening its scope for the pregnant person to receive medicines by mail and for home use ( 20 ).…”
Section: Brazil Case Studymentioning
confidence: 99%
“…Telemedicine is a model of health service delivery where providers and clients are separated by distance. It can improve the availability, accessibility, and acceptability of health care for people who experience barriers due to poverty, distance from a health care facility, or discrimination ( 19 ). It is recommended by the World Health Organization as an alternative to in-person interactions for provision of medical abortion services in whole or in part ( 17 ).…”
Section: Brazil Case Studymentioning
confidence: 99%
“…Restrictions on where abortion takes place have shifted somewhat as the use of telemedicine for a range of healthcare services has grown, and along with it, telemedicine abortion. 21 Telemedicine abortion, distinct from self-managed abortion, is when a patient consults with a healthcare provider online or by phone and acquires medicines for abortion by picking them up at a healthcare facility or pharmacy or receives them through the mail. 22 Telemedicine for abortion, however, still involves a healthcare provider, though such a requirement is not necessary for clinical safety or efficacy.…”
Section: S Elf-manag Ed Aborti On and The L Awmentioning
confidence: 99%